Remote Magnetic Nanoparticle Manipulation Enables the Dynamic Patterning of Cardiac Tissues - Zwi-Dantsis, Limor (Adv Mater, 2019)
The ability to manipulate cellular organization within soft materials has important potential in biomedicine and regenerative medicine; however, it often requires complex fabrication procedures. Here, a simple, cost-effective, and one-step approach that enables the control of cell orientation within 3D collagen hydrogels is developed to dynamically create various tailored microstructures of cardiac tissues. This is achieved by incorporating iron oxide nanoparticles into human cardiomyocytes and applying a short-term external magnetic field to orient the cells along the applied field to impart different shapes without any mechanical support. The patterned constructs are viable and functional, can be detected by T(2)*-weighted magnetic resonance imaging, and induce no alteration to normal cardiac function after grafting onto rat hearts. This strategy paves the way to creating customized, macroscale, 3D tissue constructs with various cell-types for therapeutic and bioengineering applications, as well as providing powerful models for investigating tissue behavior.